Pengaruh Komposisi Media Tanam Terhadap Pertumbuhan Tanaman Kemangi (Ocimun Basilicum L) Secara Vertikultur - Wardana, I Gede Krisna; Kartini, Ni Luh; Soniari, Ni Nengah (Nandur, 2020)
The research objective was to determine the effect of the composition of the growing medium on the growth of basil plants. This research was carried out in Banjar Dinas Belumbang Kelod, Belumbang Village, Kerambitan District, Tabanan Regency, in January-March 2020. Used was a simple randomized block design (RAK). The composition of the planting medium consisted of vermicompost fertilizer, soil and sand weighing 5 kg per treatment. The treatments tested were as follows M0: Soil + Sand (100%); M1: Soil + vermicompost fertilizer + sand (50%: 50%: 0%); M2: Soil + Kascing Fertilizer + Sand (50%: 0%: 50%); M3: Soil + vermicompost fertilizer + sand (50%: 30%: 20%); M4: Soil + Kascing Fertilizer + Sand (50%: 20%: 30%); M5: Soil + vermicompost fertilizer + sand (40%: 40%: 20%); M6: Soil + Kascing Fertilizer + Sand (40%: 30%: 30%); M7: Soil + Kascing Fertilizer + Sand (30%: 40%: 30%); M8: Soil + vermicompost fertilizer + sand (30%: 50%: 20%). The results showed that the effect of media composition gave significantly different results on plant height, fresh weight on soil, total fresh weight, dry weight above soil, total dry weight, C-organic content and microorganism population. The treatment of soil composition + vermicompost fertilizer + sand (50%: 20%: 30%) gave the best results for the growth of basil and the total population of soil microorganisms. The highest yield of fresh basil plant wet weight was 40.10 grams, an increase of 2.3% compared to the control. Then the microorganism population increased by 50% compared to the control.